1
$\begingroup$

How to integrate this?

$\int_{0}^{A} x e^{-a x^2}~ I_0(x) dx$,

where $I_0$ is modified Bessel function of first kind?

I'm trying per partes and looking trough tables of integrals for 2 days now, and I would really really appreciate some help.

This is a part of a problem, whis would be this:

$T(r,z,t)=C\int_{0}^{B} u^{-\frac{3}{2}} du \int_{0}^{A} dr_0 r_0 e^{-\frac{r^2+r_0^2+z^2}{u}}~2\pi I_0(\frac{2rr_0}{u})$

$A=constant$

$B=4Dt$

$u=4D(t-t_0)$

and if the first integral isnt solvable with something relatively not- fancy as hmm lets say Marcum Q-function (I'm a physicist i dont know what that is and how to deal with it later on in the problem), how do i go about checking out limits for this second integral? Does anyone have any ideas?

1.) $t\to \infty$

2.) $r\to0$

3.) $z=0$

$\endgroup$
  • $\begingroup$ It is very confusing for you use $u$ as both the dummy variable and the relationship of $t$ . $\endgroup$ – Harry Peter Sep 10 '16 at 11:24
0
$\begingroup$

For $\int_0^Axe^{-ax^2}I_0(x)~dx$ ,

$\int_0^Axe^{-ax^2}I_0(x)~dx$

$=\int_0^A\sum\limits_{n=0}^\infty\dfrac{x^{2n+1}e^{-ax^2}}{4^n(n!)^2}~dx$

$=\int_0^A\sum\limits_{n=0}^\infty\dfrac{x^{2n}e^{-ax^2}}{2^{2n+1}(n!)^2}~d(x^2)$

$=\int_0^{A^2}\sum\limits_{n=0}^\infty\dfrac{x^ne^{-ax}}{2^{2n+1}(n!)^2}~dx$

$=-\left[\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{x^ke^{-ax}}{2^{2n+1}a^{n-k+1}n!k!}\right]_0^{A^2}$ (according to http://en.wikipedia.org/wiki/List_of_integrals_of_exponential_functions)

$=\sum\limits_{n=0}^\infty\dfrac{1}{2^{2n+1}a^{n+1}n!}-\sum\limits_{n=0}^\infty\sum\limits_{k=0}^n\dfrac{A^{2k}e^{-aA^2}}{2^{2n+1}a^{n-k+1}n!k!}$

$=\dfrac{e^\frac{1}{4a}}{2a}-\sum\limits_{k=0}^\infty\sum\limits_{n=k}^\infty\dfrac{A^{2k}e^{-aA^2}}{2^{2n+1}a^{n-k+1}n!k!}$

$=\dfrac{e^\frac{1}{4a}}{2a}-\sum\limits_{k=0}^\infty\sum\limits_{n=0}^\infty\dfrac{A^{2k}e^{-aA^2}}{2^{2n+2k+1}a^{n+1}(n+k)!k!}$

$=\dfrac{e^\frac{1}{4a}}{2a}-\dfrac{e^{-aA^2}}{2a}\Phi_3\left(1,1;\dfrac{1}{4a},\dfrac{A^2}{4}\right)$ (according to http://en.wikipedia.org/wiki/Humbert_series)

$\endgroup$
  • $\begingroup$ Okay, first of all, wau! and thank you. could you please explain to me how you got from line 1 to 2 after the first wikipedia link...from the sum k=0 to n you somehow get the sum from k to infinity. $\endgroup$ – leia Sep 10 '16 at 21:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.